Pengaruh Model Pembelajaran Novick terhadap Kemampuan Berpikir Kritis Matematis Siswa SMA Harapan Mekar Medan - Surya Wisada Dachi; Sri Rezeki (Journal on Education, 2023)
This study aims to determine whether there is an effect of the Novick learning model on the mathematical critical thinking skills of Harapan Mekar Medan High School students in the 2022/2023 academic year. The research was conducted at Harapan Mekar Medan High School, class X IPA, with 29 students as an experimental class. This study uses a type of quantitative research with a research design that is one-group pretest-posttest design. From the results of the study, the average pretest score was 45.52 and the posttest average score was 76.21. The data analysis technique used in this study is the normality test using the Kolmogorov Smirnov test. The data being tested will be processed using the SPSS program. The gain index value of 0.6813 is interpreted into the criteria for a value of g≥0.7. The results indicate that the gain index is in the medium category. The conclusion of this study explains that there is an influence from the Novick learning model on students' mathematical critical thinking skills where there is an increase in the average value of learning outcomes after being taught using the Novick learning model.